Semi-interpenetrating polymer networks of chitosan and poly(ethylene glycol) - Milosavljević Nedeljko B.; Kalagasidis-Krušić Melina T.; Filipović Jovanka M. (Hemijska Industrija, 2008)
Chitosan is a natural polycationic polymer that possesses useful properties such as bioactivity, biocompatibility, non-toxicity and non-antigenicity. On the other hand, its mechanical properties are not good for some biomedical application. They may be improved by preparing semi-interpenetrating polymer networks (semi-IPNs), when the hydrogel network is prepared in the presence of a previously made polymer such as poly(ethylene glycol). This paper deals with synthesis and characterization of the semi-interpenetrating polymer networks of chitosan and poly(ethylene glycol) with different Ch/PEG ratio and crosslinking degree. The degree of deacetylation of chitosan was determined by potentiometric titration, titration and elemental analysis. The semi-IPNs were characterized by swelling kinetics, mechanical properties and thermal analysis. It was found that PEG content and crosslinking agent concentration significantly influence the swelling behaviour of semi-IPNs. Water uptake was higher for lower crosslinking agent concentrations and PEG contents, up to PEG/Ch = 0,75. Better mechanical strength of semi-IPNs was obtained for higher PEG content and crosslinking agent concentration. SEM analysis confirmed the porous structure of semi-IPNs. Increasing the degree of crosslinking and PEG content up to PEG/Ch = 0,75, the pore size decreased. Based on the pore size, the investigated semi-IPNs can be regarded as macroporous. Thermogravimetric analysis showed that thermal stability of the semi-IPNs depends on the degree of crosslinking, as well as on the PEG content.